Nanomechanical Characterization of Canine Femur Bone for Strain Rate Sensitivity in the Quasistatic Range under Dry versus Wet Conditions - Kun-Lin Lee; Marta Baldassarri; Nikhil Gupta; Dinesh Pinisetty; Malvin N. Janal; Nick Tovar; Paulo G. Coelho (International Journal of Biomaterials)
As a strain rate-dependent material, bone has a different mechanical response to various loads. Our aim was to evaluate the effect of water and different loading/unloading rates on the nanomechanical properties of canine femur cortical bone. Six cross-sections were cut from the diaphysis of six dog femurs and were nanoindented in their cortical area. Both dry and wet conditions were taken into account for three quasistatic trapezoid profiles with a maximum force of 2000 μN (holding time = 30 s) at loading/unloading rates of 10, 100, and 1000 μN/s, respectively. For each specimen, 254±9 (mean ± SD) indentations were performed under different loading conditions. Significant differences were found for the elastic modulus and hardness between wet and dry conditions (P<0.001). No influence of the loading/unloading rates was observed between groups except for the elastic modulus measured at 1000 μN/s rate under dry conditions (P<0.001) and for the hardness measured at a rate of 10 μN/s under wet conditions (P<0.001). Therefore, for a quasistatic test with peak load of 2000 μN held for 30 s, it is recommended to nanoindent under wet conditions at a loading/unloading rate of 100–1000 μN/s, so the reduced creep effect allows for a more accurate computation of mechanical properties.